Do older adults benefit from telepsychiatric care: Comparison to younger adults - Belanger, Heather G.; Winsberg, Mirène (Frontiers in Psychiatry, 2022)
Background Telemental health platforms may increase access to care for older adults. Historically, older adults have tended to adopt new technologies at a slower rate which creates a perception that they may not be able to benefit from them. The purpose of this study was to determine whether or not older adult patients receiving psychiatric care for depression via a telemental health platform achieve the same outcomes as younger adults. Method Participant data utilized in the current investigation were obtained from a national mental health telehealth company (i.e., Brightside) and consisted of 12,908 U.S.-based adult patients receiving psychiatric care for depression between October, 2018 and January, 2022. Propensity matching was used to create an older and younger sample (n = 141 in each) using 23 covariates. These samples were then compared using repeated measures ANOVA on Patient Health Questionnaire-9 (PHQ-9) scores at start of treatment, 6 weeks, 8 weeks, 10 weeks, 12 weeks, 14 weeks, and 16 weeks. Results Despite matching, the groups still significantly differed on prior mental health treatment, such that more older adults reported having had prior mental health treatment. There were no other differences between the groups on assessed variables. Both younger and older adults had decreasing scores over time with no significant differences between them. Conclusion Older adults have similar improvement in depression symptom severity over time following initiation of psychiatric treatment via a telehealth platform. These findings suggest that age is not a barrier to benefitting from telepsychiatric care.